Factors affecting to the success of the contemporary management accounting practices in Vietnamese enterprise - Do Huyen Trang; Le Mong Huyen (My University, 2018)
Factors affecting to the success of the contemporary management accounting practices in Vietnamese enterprise
Keywords: Management accounting; Success factors; Vietnamese enterprise